2013
DOI: 10.1186/1471-2458-13-1234
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of welfare state characteristics for health and inequalities – an analytical review

Abstract: BackgroundThe past decade has witnessed a growing body of research on welfare state characteristics and health inequalities but the picture is, despite this, inconsistent. We aim to review this research by focusing on theoretical and methodological differences between studies that at least in part may lead to these mixed findings.MethodsThree reviews and relevant bibliographies were manually explored in order to find studies for the review. Related articles were searched for in PubMed, Web of Science and Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 78 publications
(183 reference statements)
3
156
1
4
Order By: Relevance
“…Studies with a specific focus on job security, as a particularly important job quality for most people, indicate that such values are quite widespread and relatively stable over time (Clark 2005b;Esser and Olsen 2018;Gallie 2007b;Kalleberg 2009). Related comparative research on employment commitment along an intrinsic-extrinsic continuum found substantial differences between countries (Berglund 2001;Esser 2005b;Hult and Svallfors 2002), also when unemployed people were compared across countries (Gallie and Alm 2000), generally lending evidence for the existence of stronger intrinsic values in more encompassing welfare states and more regulated labor markets (Esser 2005b). Yet, existing comparative research has been based on data for specific points in time or for a relatively short time-period.…”
Section: Country Contexts and Preferencesmentioning
confidence: 99%
“…Studies with a specific focus on job security, as a particularly important job quality for most people, indicate that such values are quite widespread and relatively stable over time (Clark 2005b;Esser and Olsen 2018;Gallie 2007b;Kalleberg 2009). Related comparative research on employment commitment along an intrinsic-extrinsic continuum found substantial differences between countries (Berglund 2001;Esser 2005b;Hult and Svallfors 2002), also when unemployed people were compared across countries (Gallie and Alm 2000), generally lending evidence for the existence of stronger intrinsic values in more encompassing welfare states and more regulated labor markets (Esser 2005b). Yet, existing comparative research has been based on data for specific points in time or for a relatively short time-period.…”
Section: Country Contexts and Preferencesmentioning
confidence: 99%
“…However, the expectation that a high level of on-average population health (e.g., long life expectancy or low infant mortality) in encompassing welfare states should entail low levels of social inequality in health has not been borne out in a straightforward way (Mackenbach et al 2008), and has generated debate over relative vs. absolute measures of inequality (Brambra 2011a(Brambra , 2013, and the measurement of welfare states (Bergqvist et al 2013). This raises the intriguing possibility that the causes of on-average summary measures like infant mortality and life expectancy differ from the causes of social inequalities in health.…”
Section: Welfare States Health and Health Inequalitiesmentioning
confidence: 99%
“…Even more recently, spurred in part by newly-available, cross-nationally comparable, individual-level data (Gornick and Jaentti 2013) and new techniques for the analysis of the multilevel data (Gelman and Hill 2007;Snijders and Bosker 2012), theories of inequality are turning toward macro-scale institutions to understand how "the rules of the game" (as a common English shorthand for "institution" puts it) create "winners" and "losers" in social life (Brady 2009;Fischer et al 1996;Kenworthy 2004;Western 2006;Pettit and Hook 2009;Pontusson 2005). Institutions, as we use the term, include welfare-state policies identified by Bergqvist et al (2013) in their review of three varieties of welfare-state and health research.…”
Section: An Institutional Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy allows for examining determinants of single parents' health in a great level of detail, but typically reduces the variability in both single parents' health outcomes and social policies (as well as other contextual factors). Second, a number of studies have been based on welfare-state typologies, which makes it inherently difficult to analyse programme-specific effects of various policies related to health of single parents, as well as to analyse the impact of changes in policies over time (Bergqvist et al, 2013). Being able to do so, however, becomes increasingly important to assess the health impact of current reform developments in social policy.…”
Section: Fourteenmentioning
confidence: 99%